SOME CIRCULATION FEATURES DURING SOUTH-WEST MONSOON IN SOUTHERN VIETNAM’S WATERS - Mau, Le Dinh; Cong, Nguyen Chi; Tuan, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2017)
This paper presents some circulation features during South-West (SW) monsoon in Southern Vietnam’s waters. The data were collected from different projects which were carried out by the Institute of Oceanography in recent years. Study results show that during SW monsoon the current mostly flows from the south to the north by wind action, and it is the period of high Mekong river discharge. These conditions are the main causes of Mekong river water spreading to the Central Vietnam upwelling area. Measured data during August and September 2009 indicate that Mekong River water spreads up to about 80 km to 100 km offshore, inclining in the northern part of Mekong river mouth region towards the upwelling area. The extent of river water spreading is directly proportional to the Mekong river discharge and SW monsoon intensity. This phenomenon is significant feature for assessment of the ecological-environmental effects on the upwelling area.